Married love eaudiobook - Hadley, Tessa (Recorded Books Inc., 2013)
One of today's most accomplished storytellers, Tessa Hadley was highly praised for her New York Times Notable Book The London Train. In the collection Married Love, Hadley examines the most intimate of family relationships in situations laced with humor, warmth, and emotion.